The association between ischemic and jeopardized myocardia and all-cause mortality in patients with peripheral artery disease. (April 2016) - Hammad, Tarek A; Yousefzai, Rayan; Venkatachalam, Sridhar; Lowry, Ashley; Gornik, Heather L; Jaber, Wael; Bartholomew, John R; Kim, Soo Hyun; Cerqueira, Manuel; Gray, Bruce H; Blackstone, Eugene H; Shishehbor, Mehdi H
Peripheral artery disease (PAD) is associated with increased mortality and concomitant coronary artery disease (CAD). However, it is unclear whether uncovering the presence of functional coronary ischemia by single-photon emission computed tomography (SPECT) myocardial perfusion imaging (MPI) would further help stratifying that excess risk. From January 2000 to 2009, 4294 individuals underwent cardiac stress testing within 180 days of ankle–brachial index (ABI) measurements. Of these, 645 had PAD and SPECT MPI stress testing. Abnormal ABI was defined as ⩽0.9 or prior lower extremity arterial revascularization. Myocardial ischemic burden and total jeopardized myocardium were represented by the summed difference score (SDS) and summed stress score (SSS), respectively. Univariate and multivariable Cox proportional hazard analyses were used to study the impact of SDS and SSS on all-cause mortality. Additionally, using a hierarchical approach, we examined the step-wise addition of post-stress test coronary and lower extremity arterial revascularizations as time-varying covariates on outcomes. We found no significant difference in all-cause mortality between patients with ischemic myocardium (SDS>0) and those without (SDS=0) (adjusted HR: 0.94, 95% CI: 0.53–1.69; p =0.84). Similarly, the presence of jeopardized myocardium (SSS>0) did not have a significant impact on mortality (adjusted HR: 1.16, 95% CI: 0.67–2.00; p =0.59). Moreover, adjustment for post-testing coronary and lower extremity arterial revascularizations did not affect our results. In conclusion, ischemic and jeopardized myocardia are not predictors of all-cause mortality in PAD; thus, SPECT MPI does not appear to be a useful risk stratification tool in these patients.